DNA extraction from filter‐paper spots of vaginal samples collected after sexual violence. Issue 1 (3rd April 2014) - Campos, Elisabete A.; Pitta, Denise R.; Costa, Fernanda A.; Campos, Vanessa M.; Yela, Daniela; Fernandes, Arlete
Abstract: Objective: To detect the presence of male DNA in vaginal samples collected from survivors of sexual violence and stored on filter paper. Methods: A pilot study was conducted to evaluate 10 vaginal samples spotted on sterile filter paper: 6 collected at random in April 2009 and 4 in October 2010. Time between sexual assault and sample collection was 4–48 hours. After drying at room temperature, the samples were placed in a sterile envelope and stored for 2–3 years until processing. DNA extraction was confirmed by polymerase chain reaction for human β‐globin, and the presence of prostate‐specific antigen (PSA) was quantified. The presence of the Y chromosome was detected using primers for sequences in the TSPY (Y7/Y8 and DYS14) and SRY genes. Results: β‐Globin was detected in all 10 samples, while 2 samples were positive for PSA. Half of the samples amplified the Y7/Y8 and DYS14 sequences of the TSPY gene and 30% amplified the SRY gene sequence of the Y chromosome. Four male samples and 1 female sample served as controls. Conclusion: Filter‐paper spots stored for periods of up to 3 years proved adequate for preserving genetic material from vaginal samples collected following sexual violence.